Eisler and the ‘Coon Song’: Paper from the conference: Neue Sachlichkeit, Political Music, or Vernacular Avant-Garde? Hanns Eisler and his Contemporaries - Faßhauer, Tobias (Danish Yearbook of Musicology, 2019)
Americanism is generally regarded as an essential feature of New Objectivity, and, in the realm of music, it is usually equated with the reception of jazz. However, a closer look at the music of Krenek, Weill, and Eisler reveals that its ‘Americanist’ substance is more shaped by turn-of-the-century genres, such as the cakewalk and two-step, than by any type of American popular music of the 1920s. Thus, musical Americanism constitutes a moment of continuity that links New Objectivity to pre-war popular culture. Eisler’s Ballade vom Nigger Jim (1930) and his Niggerlied from the film Niemandsland (1931) refer in both content and music to the tradition of the minstrel song, and particularly the ‘coon song’. The coon song, a vocal genre close to ragtime and essentially based on racist stereotypes, found reverberations in Germany at the beginning of the 20th century, e.g. in Walter Kollo’s Das kleine Niggergirl (1908), and had an even longer life there than in the United States. A comparative analysis demonstrates how Eisler’s ‘coon songs’, and especially Nigger Jim, turn the genre and its racist implications against themselves. Through textual elements and compositional procedures, the coon song is ‘refunctioned’ (umfunktioniert), as Eisler would have put it. In the case of his coon songs, then, the idiomatic backwardness in relation to contemporaneous American music proves to be an instance of artistic calculus.